2017
DOI: 10.1177/0022034517722761
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Genes for Nonsyndromic Cleft Palate Detected by Exome Sequencing

Abstract: Nonsyndromic cleft palate only (nsCPO) is a facial malformation that has a livebirth prevalence of 1 in 2,500. Research suggests that the etiology of nsCPO is multifactorial, with a clear genetic component. To date, genome-wide association studies have identified only 1 conclusive common variant for nsCPO, that is, a missense variant in the gene grainyhead-like-3 ( GRHL3). Thus, the underlying genetic causes of nsCPO remain largely unknown. The present study aimed at identifying rare variants that might contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Along with IRF6 , GRHL3 is essential to a functional oral periderm, and a failure of this process contributes to Van der Woude syndrome (Peyrard‐Janvid et al., ). The GRHL3 mutation (NM_198173:c.‐187G>A) identified in our study was also reported in a previous study in a patient with only nonsyndromic CP (Hoebel et al., ). Multiple study designs and statistical approaches could be used to address the rare variant hypothesis for NSCLP (Leslie et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…Along with IRF6 , GRHL3 is essential to a functional oral periderm, and a failure of this process contributes to Van der Woude syndrome (Peyrard‐Janvid et al., ). The GRHL3 mutation (NM_198173:c.‐187G>A) identified in our study was also reported in a previous study in a patient with only nonsyndromic CP (Hoebel et al., ). Multiple study designs and statistical approaches could be used to address the rare variant hypothesis for NSCLP (Leslie et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…13,17 The cleft palate present in our patient is a very unusual finding within the MLS spectrum, having been reported only once in a patient with lower limb linear skin defects and no identifiable abnormalities in karyotype or microarray. 7 There is no known candidate gene for nonsyndromic cleft palate in the Xp22.3p22.2 region, 24,25 however, pathogenic variants and deletions in some genes in this region, such as ANOS1 and MID1, result in syndromic orofacial cleft. ANOS1, also called KAL1, is the first gene found to be responsible for Kallmann syndrome, 26 a heterogeneous genetic condition characterized by hypogonadotropic hypogonadism with anosmia.…”
Section: Discussionmentioning
confidence: 99%
“…This definition of the associated dental phenotype is also important because several authors have previously emphasized the importance of a correct clinical diagnosis of volunteers for genetic studies involving clefts, particularly with regard to VWS, characterized by the presence of orofacial clefts, lower lip pits, and dental agenesis (in 25% of cases) (Chen et al, ; Hoebel et al, ; Rutledge et al, ; Zucchero et al, ). For this reason, in the present study, oral photographs and familial history were reviewed in all cases where novel or rare variations were identified in order to confirm no alterations in the lower lip and no familial history for cleft or other alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Cleft lip and palate (CLP) is the most common orofacial malformation and is classified as either non‐syndromic or syndromic according to whether they form part of a broader disorder or phenotype associated with other morphological anomalies (Gowans et al, ; Rahimov, Jugessur, & Murray, ). Approximately 70% of the orofacial cleft cases are non‐syndromic (NS) with multifactorial etiology including both genetic and environmental factors (Hoebel et al, ). These factors confound attempts to identify specific genes for the anomaly (Leslie et al, ).…”
Section: Introductionmentioning
confidence: 99%